Innovation of Micro Equity Model for Msme Business Adaptation During Pandemic Covid-19. - Bambang Dwi Hartono; Ahmad Diponegoro; Indra Yuliawan (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Large number of MSMEs have been severely hit during the Covid-19 pandemic. This study examined a micro equity financing model as an innovative answer to conventional micro loan in assisting MSMEs’ bussiness adaptation during the pandemic. The micro equity financing model employs a profit-sharing system with flexible repayment method and without collateral. A qualitative descriptive data processing approach was employed. Due to pandemic situation, interviews were conducted online to respondents of MSME that use the micro equity model in the Equitree project in Yogyakarta. The micro equity model has shown to provide many benefits to MSME business adaptation, especially in financial, marketing and product aspects, such as innovation in product development, online marketing, business assistance, flexible repayment and easier loan application.